Crowdsourced employer branding: an analysis from the platform glassdoor - Penz, Daniel; Almeida, Mathias Picollo de; Amorim, Bianca Costa; Cembranel, Priscila; Rolt, Carlos Roberto de (Revista de Administração da UFSM, 2023)
Purpose: The present study aims to evaluate the aspects of organizational climate and culture from the voluntary contributions published in the Crowdsourced Employer Branding Glassdoor. Design/methodology: Methodologically, this is an applied, descriptive longitudinal retrospective research, with a quantitative and qualitative approach to data, whose collection took place by means of a technical survey procedure with interpretative analysis of Glassdoor users' statements. The sample was composed of 5 companies from the technological sector located in the city of Florianópolis-SC. Findings: The study investigates the organizational culture from the observations obtained on Glassdoor, verify the difference in averages between Culture and General Note of the companies observed, the perception of climate from the manifestations in favor or against the practices of the organization and relate the culture and organizational climate of the sample studied. Originality/value: Theoretically, the study points out the possibilities of evaluating the organizational climate and culture through Crowdsourced Employer Branding platforms and that the "culture" factor is a determining factor for the positive or negative evaluation of a company. In relation to practical contributions, it can be seen that the study contributes to the decision of candidates about which companies to work for. In addition, it brings the importance of companies developing a good culture and maintaining a good organizational climate. Considering that this information is accessible to people on the internet.